Effectiveness of waste water treatment system for palm oil mill effluent (POME) / Rosliana Razali - Razali, Rosliana (2006)
Malaysia is one of the countries leading in producing and exporting palm oil. These large activities produced large quantities of high strength palm oil mill effluent (POME). Beside palm oil industry contributes to environmental problems through their effluent. Waste water system must be treated to reduce the volume of effluent. Within this research are to identify the effectiveness of waste water treatment system for POME according to the parameter limits from the watercourse discharge like as BOD,COD, SS and pH, and then the parameter will be compare with parameter from Environment Quality Act 1974 (EQA). This research also to identify the efficient treatment system of POME varies with the type of treatment. The two type of treatment was compared is a ponding system from Kalumpung Oil Mill with open digester tank system at Chersonese Oil Mill. Sample of effluent from the POME were tested according to parameter of BOD, COD, SS and pH in a laboratory. In the standard B of watercourse limit the pH range are 5-9, BOD values must be equal or less then 100mg/l, COD values must not exceed 1000mg/l, and SS value 100mg/l. From the comparing result showed that both of the waste water treatment system in a both palm oil is followed the EQA 1974 and the waste water treatment system are effective and the most efficient treatment system is open digester tank and this will be showed from the result of BOD and COD from final discharge.